Analisis Kandungan Pupuk Organik Cair Kulit Nanas dengan Metode Atomic Absorbsion Spektrophotometri dan Automated Wet Chemistry Analyzer - Dalimunthe, Gunawan Syahputra; Lestari, Widya; Rizal, Khairul (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2023)
Research on the analysis of liquid organik fertilizer content from pineapple waste with the AAS (Atomic Absorbsion Specophotometry) and (Automated Wet Chemistry Analyzer) methods of research to find out the levels of N, P and K in pineapple skin waste with the AAS (Atomic Absorbsion Specophotometry) method and automated wet chemistry analyzer tool. This research was conducted at the Laboratory of PT. Socfindo Indonesia analyst. The study was conducted on May 16, 2019. This research is descriptive, where the first process is the process of making organik fertilizers derived from pineapple skin waste fermented for 30 days that samples of liquid organik fertilizer pineapple skin waste are tested in lab tools, With the Automed and ASS method is still in the safe stage or can be given to plants that later this liquid organik fertilizer can play a direct role against the plant. Keywords: Level Analysis, Fertilizers N, P and K